HUKUM EKONOMI SYARIAH : TELAAH REGULASI PENERBITAN SUKUK IJARAH - Nunung Rodliyah; Ade Oktaritas KY; Ricco Andreas (Postgraduate State Islamic Institute (IAIN) Metro, 2018)
The investment discussed in this study is an example of investment activities in the Islamic capital market. Indonesia, which has the potential of being a majority Muslim population, is expected to be able to accommodate and actively participate as the main perpetrators of Indonesia's sharia capital market, which is supported by regulations as a counterweight to capital market transaction activities.In this study, legal issues are explained systematically in the form of the first problem formulation, what are the forms of regulations and the mechanisms that are applied in the issuance of ijarah sukuk, secondly the legal context of parties in the issuance of sukuk based on ijarah agreement. The type of research used in this research is normative, with descriptive research type.The problem approach used is inventorying legal material (data) the results of processing for the study were analyzed using qualitative analysis methods, by producing a description of the data in the form of sentences arranged in a regular, logical, and effective manner. The results of this study are 1.) Sukuk transactions in Indonesia are regulated in several regulations, namely the Law, OJK Regulations, and Fatwa. Regarding the mechanism for issuing sukuk, it follows the procedure based on the Ijarah agreement which is governed by Islamic law. 2.) The legal context of the parties to the sukuk transaction includes the rights and obligations of the parties, which are governed by the provisions of both national positive law and Islamic law.